Trustworthiness in the Financial Industry - Andrej Gill; Matthias Heinz; Heiner Schumacher; Matthias Sutter (Institute of Labor Economics (IZA), 2020)
The financial industry has been struggling with widespread misconduct and public mistrust. Here we argue that the lack of trust into the financial industry may stem from the selection of subjects with little, if any, trustworthiness into the financial industry. We identify the social preferences of business and economics students, and follow up on their first job placements. We find that during college, students who want to start their career in the financial industry are substantially less trustworthy. Most importantly, actual job placements several years later confirm this association. The job market in the financial industry does not screen out less trustworthy subjects. If anything the opposite seems to be the case: Even among students who are highly motivated to work in finance after graduation, those who actually start their career in finance are significantly less trustworthy than those who work elsewhere.
Keywords: C91; G20; M51; 330; trustworthiness; financial industry; selection; social preferences; experiment